(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Measles is a childhood infection caused by a virus. Once quite common, measles can now almost always be prevented with a vaccine. Also called rubeola, measles spreads easily and can be serious and even fatal for small children. While death rates have been falling worldwide as more children receive the measles vaccine, the disease still kills more than 200,000 people a year, mostly children.